Practice standard for project configuration management (Project Management Institute, 2007)
Most projects present teams with challenges relating to time, cost and scope. Careful management of these project elements allows projects to be completed successfully. In order to guide a project's direction, project managers utilize the process of configuration management. Project configuration management is the collective body of processes, activities, tools, and methods used to manage certain items during the project lifecycle. Configuration management is implemented to actively guide the direction of the project and support communication that will facilitate successful completion. Due to the increasing complexity of projects and greater competition among companies, the knowledge of configuration management techniques is more important than ever.